A Strategic Model for Technical Talent Management: A Model Based on a Qualitative Case Study. Issue 4 (2014) - Kim, Yeonsoo; Williams, Rachele; Rothwell, William J.; Penaloza, Paul
Abstract One critical challenge for organizations today is building and sustaining a strong talent pipeline through effective management of human assets. Talent management focuses on developing talent that is strategically important for an organization's future. Research in talent management typically focuses on managerial or leadership talents, yet there are other important career tracks within an organization. Although preparing employees for promotion into management remains critically important, technical expertise such as engineering is often the key competitive advantage in the global knowledge economy. Research has repeatedly emphasized that technical workers look for different things. But most of the studies concerning technical talent management focus on the management of technical professionals and experts in isolation. This study was undertaken to address unique problems in attracting, developing, retaining, and transferring the knowledge of engineers, whose abilities are critical in a knowledge or innovation economy. Through in‐depth interviews with selected best practice companies on how they operate their technical talent management system and programs, the study examined shared characteristics of selected organizations with programs geared to engineers. The results are summarized in a systematic model that describes common elements of effective technical talent management programs.